(untitled) - Latham-Koenig, Christina (Oxford, 2015)
The English File Third Edition Teacher's Book offers a comprehensive walk-through guide to every lesson, in every unit of the English File Third Edition Student's Book, along with over 70 photocopiable activities.
Keywords: Anh ngữ,English language; Dạy và học,Nói tiếng nước ngoài,Study and teaching,Foreign speakers